The influence of prey distribution on marine top predator movements - Vogel, Emma (UiT The Arctic University of Norway, 2023)
Predation is an ecological process that relies on spatial and temporal co-occurrence of predators and their prey. In marine ecosystems, killer and humpback whales are considered sentinels of ecosystem health, given their critical roles as top predators in shaping marine food webs and their responsiveness to ecosystem changes. As they are seldom influenced by natural threats, they are model species for the study of predator-prey dynamics since their movements, as observed by multidimensional biotelemetry, can reveal interactions occurring underwater and out of sight. This thesis is comprised of three papers that investigate how various prey influences the movements of killer and humpback whales within the Norwegian and Barents Seas. Paper I combined herring density data with whale satellite telemetry to explore how killer whale movements respond to patchy distributions of Norwegian spring spawning herring. This revealed that killer whales follow herring along the Norwegian coast, adjusting their movements in response to herring density. Paper II examined movement differences associated with Norwegian killer whale seal predation as compared to fish predation. Differences in travel routes, shore proximity, and directionality towards seal haul-out areas were observed, emphasizing how these predators optimize their foraging strategies for their prey. Paper III investigated how humpback whale horizontal and vertical movements were influenced by capelin density in the Barents Sea. Both lateral and vertical whale movements responded to capelin density variations, highlighting their tendency to target the densest prey aggregations on both horizontal and vertical scales. Collectively, this thesis revealed nuanced foraging movements in response to varying prey distributions, underscoring the need for more comprehensive models to account for the complexities of predator-prey dynamics, particularly in the face of the rapidly changing Arctic marine ecosystems. It also serves as a foundation for future research incorporating ...